The Impact of Corporate Philanthropy on Reputation for Corporate Social Performance - Gardberg, Naomi A.; Zyglidopoulos, Stelios C.; Symeou, Pavlos C. (My University, 2019)
This study seeks to examine the mechanisms by which a corporation’s use of philanthropy affects its reputation for corporate social performance (CSP), which the authors conceive of as consisting of two dimensions: CSP awareness and CSP perception. Using signal detection theory (SDT), the authors model signal amplitude (the amount contributed), dispersion (number of areas supported), and consistency (presence of a corporate foundation) on CSP awareness and perception. Overall, this study finds that characteristics of firms’ portfolio of philanthropic activities are a greater predictor of CSP awareness than of CSP perception. Awareness increases with signal amplitude, dispersion, and consistency. CSP perception is driven by awareness and corporate reputation. The authors’ contention that corporate philanthropy is a complex variable is upheld, as we find that CSP signal characteristics influence CSP awareness and perception independently and asymmetrically. The authors conclude by proposing avenues for future research.
Keywords: Corporate philanthropy; Corporate reputation; Corporate social performance; Signal detection theory